Black soybean seed coat polyphenol ameliorates the abnormal feeding pattern induced by high-fat diet consumption - Hironao, Ken-yu; Ashida, Hitoshi; Yamashita, Yoko (Frontiers in Nutrition, 2022)
High-fat diet (HFD) consumption induces chronic inflammation and microglial accumulation in the mediobasal hypothalamus (MBH), the central regulator of feeding behavior and peripheral metabolism. As a result, the diurnal feeding rhythm is disrupted, leading to the development of obesity. Diet-induced obesity (DIO) can be prevented by restoring the normal feeding pattern. Therefore, functional foods and drugs that ameliorate hypothalamic inflammation and restore the normal feeding pattern may prevent or ameliorate DIO. Numerous functional foods and food-derived compounds with anti-obesity effects have been identified; however, few studies have been performed that assessed their potential to prevent the HFD-induced hypothalamic inflammation and disruption of feeding rhythm. In the present study, we found that polyphenols derived from black soybean seed coat (BE) significantly ameliorated the accumulation of activated microglia and pro-inflammatory cytokine expression in the arcuate nucleus of the hypothalamus of HFD-fed mice, and restored their feeding pattern to one comparable to that of standard diet-fed mice, thereby ameliorating DIO. Furthermore, cyanidin 3-O-glucoside—the principal anthocyanin in BE—was found to be a strong candidate mediator of these effects. This is the first study to show that BE has the potential to provide a variety of beneficial effects on health, which involve amelioration of the HFD-induced hypothalamic inflammation and abnormal feeding pattern. The results of this study provide new evidence for the anti-obesity effects of black soybean polyphenols.